Non-specific inflammatory bowel disease - Vargas Machuca-Carranza, Christian Alberto (2020)
Non-specific inflammatory bowel disease refers to a group of diseases which at the time of diagnosis cannot be classified as Crohn’s disease or ulcerative colitis, and it representsapproximately up to 15% of inflammatory bowel diseases. We present the case of a patient who started with chronic abdominal pain who progressed to intestinal perforation dueto an ileal inflammatory process, that it could not be identified a cause after many studies and, added to the characteristics of the pathological anatomy, it was concluded that it was a case of non-specific inflammatory bowel disease.